Ngalap Berkah Qur’an: Dampak Membaca Al-Qur’an Bagi Para Pembacanya - Eva Nugraha (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2018)
This paper examines the question of how the impact of reading the Qur'an in everyday life? The author uses the word impact as diction to show that the Qur'an as dhikr mubārak / Kitābun mubārak, has blessings. This research is a development of one of the sub-chapters of the author's dissertation draft regarding the blessings of the Qur'an. The data used are the results of interviews and observations on a number of readers and memorizers of the Qur'an. Data were analyzed by using qualitative approach, starting from data coding, description of coding result and classification. The author uses the framework of the exegete's on mubārak/ Quranic blessing which are the definition, terms and benefits of the blessings of the Qur'an. As for the conclusion of this paper is: that the impact of reading the Qur'an will depend on the intensity and pattern of reader interaction to the Qur'an. There are two effects that readers get from their interactions in reading the Qur'an. first direct impact, which corresponds to the motive and purpose of reading, such as peace of mind. Second: the indirect impact, such as ease in living life.